BUSINESS LICENSING CHALLENGES IN WEST JAVA FROM AN ADMINISTRATIVE LAW PERSPECTIVE - Taty Sugiarti; Berna Sudjana Ermaya (PT. Radja Intercontinental Publishing, 2024)
The transformation of risk-based business licensing through the Online Single Submission (OSS) system is intended to accelerate services and strengthen legal certainty, yet digitalization does not eliminate the administrative-law dimensions of license issuance, verification, supervision, and dispute handling. This study examines business licensing problems in West Java following the enactment of Government Regulation Number 28 of 2025 and West Java Provincial Regulation Number 4 of 2025. It applies normative legal research using statutory and conceptual approaches, supported by secondary evidence from OSS-RBA implementation studies in several West Java localities. The study identifies five major problems: the need to harmonize regulations and central-local delegation instruments; an insufficiently explicit chain of accountability for digital decisions and service disruptions; uneven user and administrative capacity; challenges in data interoperability, business classification, spatial planning, and environmental requirements; and risk-based supervision that must balance easier licensing. From an administrative-law perspective, these issues directly concern the principles of legal certainty, due care, openness, non-abuse of authority, public interest, and good service. The study concludes that licensing reform in West Java should prioritize regulatory harmonization, measurable allocation of responsibilities, assisted digital services, auditable decision trails, stronger complaint and administrative-remedy mechanisms, and supervision proportionate to business risk.